WRITTEN PRODUCTION IN ENGLISH LANGUAGE AND GENERATIVE ARTIFICIAL INTELLIGENCE: REFLECTIONS ON THE USE OF CHATGPT WITH UNDERGRADUATE ENGLISH STUDENTS IN MAUÉS/AMAZONAS (REMUNOM, 2026)
This paper presents a case study with undergraduate students of English Language Mediated by Technology at the State University of Amazonas (UEA), in the municipality of Maués (AM), during the Written Production in English Language subject. Although the course objective did not foresee the use of Artificial Intelligence (AI), the professor proposed integrating it as a complementary resource to support academic production in English. The study seeks to reflect on how generative AI can influence learning, motivate critical thinking, and improve writing skills, grounding this practice to the concept of World English (Crystal, 2004). The research, with a qualitative approach, is configured as a case study (Gil, 2008), exploratory and descriptive. The methodological path involved the following stages: (1) initial writing; (2) application of AI for correction; and (3) use of AI for text improvement. Testimonials, written productions, and teaching observations allowed analysing changes in students' posture and perceptions. The methodological design incorporated elements of the Technology Acceptance Model (TAM) and active learning, encouraging the critical use of AI. The results indicate that the undergraduates recognized repertoires and limitations, understanding AI as an instrument to strengthen writing, expand linguistic awareness, and integrate into the global communication network, even in Amazonian contexts.